Following the Clues: Usefulness of Biomarkers of Neuroinflammation and Neurodegeneration in the Investigation of HTLV-1-Associated Myelopathy Progression - Souza, Flávia dos Santos; Freitas, Nicole Lardini; Gomes, Yago Côrtes Pinheiro; Torres, Rafael Carvalho; Echevarria-Lima, Juliana; Silva-Filho, Isaac Lima da; Leite, Ana Claudia Celestino Bezerra; Lima, Marco Antonio Sales Dantas de; Silva, Marcus Tulius Teixeira da; Araújo, Abelardo de Queiroz Campos; Espíndola, Otávio Melo (Frontiers in Immunology, 2021)
Human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurodegenerative disease due to axonal damage of the corticospinal secondary to an inflammatory response against infected T-cells. In the present work, we aimed to evaluate biomarkers of neurodegeneration and neuroinflammation in the definition of HAM/TSP prognosis. Neurofilament light (NfL) and phosphorylated heavy (pNfH) chains, total Tau protein, cellular prion protein (PrPc), inflammatory chemokines, and neopterin were quantified in paired cerebrospinal fluid (CSF) and serum samples from HAM/TSP patients (n=21), HTLV-1 asymptomatic carriers (AC) (n=13), and HTLV-1 seronegative individuals with non-inflammatory non-degenerative neurological disease (normal-pressure hydrocephalus) (n=9) as a control group. HTLV-1 proviral load in peripheral blood mononuclear cells and the expression of chemokine receptors CCR4, CCR5, and CXCR3 in infected CD4+ T-cells (HTLV-1 Tax+ cells) were also assessed. CSF levels of Tau, NfL, and pNfH were similar between groups, but PrPc and neopterin were elevated in HAM/TSP patients. Most individuals in the control group and all HTLV-1 AC had CSF/serum neopterin ratio < 1.0, and two-thirds of HAM/TSP patients had ratio values > 1.0, which positively correlated with the speed of disease progression and pNfH levels, indicating active neuroinflammation. HAM/TSP patients showed high serum levels of CXCR3-binding chemokines (CXCL9, CXCL10, and CXCL11) and elevated CSF levels of CCL2, CCL3, CCL4, CCL17, CXCL5, CXCL10, and CXCL11. Indeed, CXCL10 concentration in CSF of HAM/TSP patients was 5.8-fold and 8.7-fold higher in than in HTLV-1 AC and controls, respectively, and correlated with CSF cell counts. HAM/TSP patients with typical/rapid disease progression had CSF/serum CXCL10 ratio > 1.0 and a higher frequency of CXCR3+Tax+CD4+ T-cells in blood, which indicated a positive gradient for the migration of infected cells and infiltration into the central nervous system. In conclusion, the slow progression of HAM/TSP abrogates the usefulness of biomarkers of neuronal injury for the disease prognosis. Thus, markers of inflammation provide stronger evidence for HAM/TSP progression, particularly the CSF/serum neopterin ratio, which may contribute to overcome differences between laboratory assays.